Comparison of BLDC Motor Control with Fuzzy Tuning by Solar Power Input and Zeta Converter - D V V V Ch Mouli, Dr.; Padmasri, K. (International Journal of Engineering and Technology, 2018)
The importance of brushless DC (BLDC) motorÂ Â along with its control is enhancing in present days due to its wide applications in sophisticated equipments. In this paper various parameters of the BLDC Motor was observed using open loop and closed feedback loop with Fuzzy and PI control. With the help of observed parameters, better controlling techniques are applied to BLDC Motor control. Solar power is used with Zeta converter in boost mode to give the power supply to the Motor. Using DC Generator the electrical loading is applied on BLDC Motor. The effect of closed loop control on Zeta converter was also analyzed. In present days the BLDC Motor drives are widely usingÂ Â in aviation, defense, etc due to absence of commutator sparks. So high priority for better control of BLDC Motor in coordination with embedded designs is given due to its increasing utilization.Â Â